MYO1C stabilizes actin and facilitates the arrival of transport carriers at the Golgi complex - Capmany, Anahi (2019)
In this study, we aimed to identify the myosin motor proteins that control trafficking at the Golgi complex. In addition to the known Golgi-associated myosins MYO6, MYO18A and MYH9 (myosin IIA), we identified MYO1C as a novel player at the Golgi in a human cell line. We demonstrate that depletion of MYO1C induces Golgi complex fragmentation and decompaction. MYO1C accumulates at dynamic structures around the Golgi complex that colocalize with Golgi-associated actin dots. MYO1C depletion leads to loss of cellular F-actin, and Golgi complex decompaction is also observed after inhibition or loss of the actin-related protein 2/3 complex, Arp2/3 (also known as ARPC). We show that the functional consequence of MYO1C depletion is a delay in the arrival of incoming transport carriers, both from the anterograde and retrograde routes. We propose that MYO1C stabilizes actin at the Golgi complex, facilitating the arrival of incoming transport carriers at the Golgi.This article has an associated First Person interview with the first author of the paper.